Keanekaragaman Jenis Tanaman Pekarangan di Desa Antibar Kecamatan Mempawah Timur Kabupaten Mempawah - Riza Linda, Syech Novi Andriansyah, Irwan Lovadi (Jurnal Protobiont, 2015)
The courtyard is a land plot of land located immediately around the house and clear boders, planted with one or various types of plants and still has the ownership and functional relationship with the residents concerned. This research aims to know the kinds of plants and lawns as well as the diversity of the plant communitystructure on the grounds of the house with a different area in the village of Antibar. This research was conducted in May 2014 until August 2014. Sampling location research done by the method of stratified random sampling. The results showed that there are 79 species that belongs to the plant species in six plants plant taxonomy namely Magnoliopsida, Liliopsida, Pinopsida, Gnetopsida, Cycadopsida and Lycopodiopsida. The density of the plants have the highest value in the narrow yard type and the value of the highest frequency on the spacious grounds of the type. The grounds of the plant community structure belongs to have diversity (H êžŒ ) type is high. Composition of plant type between the grounds are spacious and have a high similarity level compared to the other pair of spacious lawns. The form depends on the utilization of wide lawns residents. The grounds are spacious, and the villagers Antibar tend to make use of the grounds to ornamental plants.